2011
DOI: 10.1249/mss.0b013e31820618d3
|View full text |Cite
|
Sign up to set email alerts
|

Venous and Arterial Bubbles at Rest after No-Decompression Air Dives

Abstract: Our findings indicate high amounts of gas bubbles produced after no-decompression air dives based on standardized diving protocols. High bubble loads were frequently associated with the crossover of VGE to the systemic circulation. Despite these findings, no acute decompression-related pathology was detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 19 publications
1
47
1
Order By: Relevance
“…Also, as in our recent studies, we found crossing of gas bubbles to systemic arterial side. These arterializations occurred more often after air dives as compared to nitrox (seven vs. two arterializations, respectively), which could be explained by the higher overall bubble load after air diving (Ljubkovic et al , 2011. However, despite higher gas bubbling after air dives, nitrox diving had greater impact on endothelial function, as evidenced by signiWcantly reduced FMD response after nitrox diving.…”
Section: Figmentioning
confidence: 93%
“…Also, as in our recent studies, we found crossing of gas bubbles to systemic arterial side. These arterializations occurred more often after air dives as compared to nitrox (seven vs. two arterializations, respectively), which could be explained by the higher overall bubble load after air diving (Ljubkovic et al , 2011. However, despite higher gas bubbling after air dives, nitrox diving had greater impact on endothelial function, as evidenced by signiWcantly reduced FMD response after nitrox diving.…”
Section: Figmentioning
confidence: 93%
“…These studies were conducted at rest and after arm or leg exercise to elicit bubble release from vascular margins, exactly as described in our previous report (25). Bubble grading employed a modified Brubakk scale that has been used in several studies (12). The grading system is as follows: 0, no bubbles; 1, occasional bubbles; 2, at least one bubble every four cardiac cycles; 3, at least one bubble every cardiac cycle; 4, continuous bubbling with modifiers [(a ϭ at least one bubble per cm 2 in all frames), (b ϭ at least three bubbles per cm 2 in all frames), or (c ϭ almost complete "whiteout" but individual bubbles can still be discerned)] and 5, whiteout where individual bubbles cannot be discerned.…”
Section: Subjectsmentioning
confidence: 99%
“…The central place of bubbles as an inciting factor for DCS is widely accepted, yet most decompression procedures generate asymptomatic blood-borne bubbles (4,12,13). Inert gases inhaled while breathing are taken up by tissues in proportion to the ambient pressure, and when pressure is reduced, some of the gas released from tissues forms bubbles due to the presence of gas cavitation nuclei (6,33,34).…”
mentioning
confidence: 99%
“…DCS is the term used when clinical symptoms of this transition manifest in humans. While bubbles are thought to be the precursor for the development of DCS, particularly if within the arterial circulation (Ljubkovic et al, 2011), the presence of gas bubbles alone does not indicate that DCS has, or will, develop (Brubakk and Eftedal, 2001; Barak and Katz, 2005; Ljubkovic et al, 2011). Symptoms experienced in human DCS cases are very varied and non-specific, and are dependent on where gas bubbles lodge and the degree of tissue damage caused.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary mechanisms include activation of the complement cascade or activation of inflammatory pathways (Kayar et al, 1997; Thom et al, 2011). These pathways are an area of great interest in human DCS studies and are triggered via endothelial damage and the release of microparticles (small vesicles or fragments that are released from stressed or damaged endothelium and circulate in the blood) in response to decompression stress (Barak and Katz, 2005; Brubakk et al, 2005; Ljubkovic et al, 2011; Thom et al, 2011). Multiple risk factors have been modeled to investigate what factors result in the development of DCS in humans subsequent to gas bubble formation, but the process remains poorly understood (Weathersby et al, 1984, 1992; Pilmanis et al, 2004; Barak and Katz, 2005).…”
Section: Introductionmentioning
confidence: 99%